Pemberian Bubur Tempe terhadap Lamanya Diare Akut pada Balita di Puskesmas Puruk Cahu - Happy Marthalena Simanungkalit; Muliana Muliana (Politeknik Kesehatan Kemenkes Mamuju, 2021)
Diarrhea is currently still the third leading cause of under-five mortality after pneumonia. Diarrhea is one of the diseases that causes death and illness in toddlers every year. One result of diarrhea is nutritional disorders due to reduced food intake, vomiting, hypoglycemia, dehydration which causes metabolic balance disorders because fluid intake is not balanced with expenditure through vomiting and diarrhea. The purpose of this study was to determine the difference in the duration of diarrhea when giving tempeh porridge to toddlers at the Puruk Cahu Health Center. The design of this study is analytic research with this type of research is Quasi Experiment using the design of the Group Control Post Test Only Design. The population in this study were toddlers who had acute diarrhea in the working area of ​​Puruk Cahu Health Center, Murung Raya Regency and the sample size was 38 people (19 people as the control group and 19 experimental groups). The statistical test used in this study was the Mann Whitney test. The results of statistical tests using the Mann Whitney test found that p value = 0.002 means the value of p value < alpha (0.05), meaning that there is an effect of giving tempe porridge to the duration of diarrhea at Puruk Cahu Health Center. Diarrhea in the group that was not given tempeh porridge lasted longer than the group that was given tempeh porridge. The Conclusion is that there is a difference in the duration of acute diarrhea in the administration of tempe porridge for toddlers at the Puruk Cahu Health Center.